2015
DOI: 10.1177/0194599815581613
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Papillary Squamous Cell Carcinoma

Abstract: This analysis of the largest sample of LPSCC demonstrates a better prognosis for this pathology compared with other laryngeal malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The survival rate of LC differs in different regions. Survival rate is influenced by many factors such as T stage, N stage, tumor location, and differentiation degree [ 22 24 ], while some conclusions were different such as the nutritional status of patients before treatment, smoking and drinking history, and treatment options. Many researchers have indicated that Cox proportional hazards analysis results revealed that T stage, pathological differentiation, and N stage were independent factors that affect the prognosis of LC.…”
Section: Resultsmentioning
confidence: 99%
“…The survival rate of LC differs in different regions. Survival rate is influenced by many factors such as T stage, N stage, tumor location, and differentiation degree [ 22 24 ], while some conclusions were different such as the nutritional status of patients before treatment, smoking and drinking history, and treatment options. Many researchers have indicated that Cox proportional hazards analysis results revealed that T stage, pathological differentiation, and N stage were independent factors that affect the prognosis of LC.…”
Section: Resultsmentioning
confidence: 99%
“…In this variant, a 7:1 male predominance was observed, with the majority of cases presenting in white races [ 13 ]. Findings from another study on a rare distinct entity of laryngeal cancer from typical SCC, namely laryngeal papillary SCC over 1973–2011 in the US, demonstrated that this histopathological subtype corresponds to 0.5% of all laryngeal tumors, with a 3:1 male predominance and no racial preference; however, the incidence trends were not investigated [ 12 ]. Reports from another rare variant of laryngeal cancer, laryngeal adenocarcinoma not otherwise specified, which refers to variants of minor salivary gland tumors of the larynx that do not align with other established histological subtypes, demonstrated an overall incidence of 0.008 per 100,000 within 2000–2012, with males (80.2%) and whites (84.7%) constituting the majority of cases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal squamous cell carcinoma is one of the most common malignant tumors, accounting for 14% of head and neck tumors, while squamous carcinoma is the most common type of laryngeal cancer, accounting for about 93-99% of laryngeal cancer 1,2 . Over the past 40 years, the incidence of laryngeal squamous cell carcinoma has declined steadily, while the 5-year survival rate has not improved signi cantly, especially in the advanced stage, where early symptoms are not signi cant and about 60% of patients are not diagnosed until the advanced stage (stage III or IV) 3,4 . Due to the characteristics of occultation, invasiveness, recurrence and metastasis, it has low sensitivity to chemo/radiotherapy, strong resistance and poor curative effect.…”
Section: Introductionmentioning
confidence: 99%